Answer: OPTION C
Step-by-step explanation:
Remember that:
![\sqrt[n]{a^n}=a](https://tex.z-dn.net/?f=%5Csqrt%5Bn%5D%7Ba%5En%7D%3Da)
And the Product of powers property establishes that:
![a^m*a^n=a^{(mn)}](https://tex.z-dn.net/?f=a%5Em%2Aa%5En%3Da%5E%7B%28mn%29%7D)
Rewrite the expression:
![\frac{\sqrt{18x} }{\sqrt{32} }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B18x%7D%20%7D%7B%5Csqrt%7B32%7D%20%7D)
Descompose 18 and 32 into their prime factors:
![18=2*3*3=2*3^2\\32=2*2*2*2*2=2^5=2^4*2](https://tex.z-dn.net/?f=18%3D2%2A3%2A3%3D2%2A3%5E2%5C%5C32%3D2%2A2%2A2%2A2%2A2%3D2%5E5%3D2%5E4%2A2)
Substitute into the expression, then:
![\frac{\sqrt{(2*3^2)x} }{\sqrt{2^4*2} }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B%282%2A3%5E2%29x%7D%20%7D%7B%5Csqrt%7B2%5E4%2A2%7D%20%7D)
Finally,simplifying, you get:
![\frac{3\sqrt{(2)x} }{2^2\sqrt{2} }=\frac{3\sqrt{2x}}{4\sqrt{2}}=\frac{(3)(\sqrt{x})(\sqrt{2})}{(4)(\sqrt{2})}= \frac{3\sqrt{x}}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B3%5Csqrt%7B%282%29x%7D%20%7D%7B2%5E2%5Csqrt%7B2%7D%20%7D%3D%5Cfrac%7B3%5Csqrt%7B2x%7D%7D%7B4%5Csqrt%7B2%7D%7D%3D%5Cfrac%7B%283%29%28%5Csqrt%7Bx%7D%29%28%5Csqrt%7B2%7D%29%7D%7B%284%29%28%5Csqrt%7B2%7D%29%7D%3D%20%5Cfrac%7B3%5Csqrt%7Bx%7D%7D%7B4%7D)
7.772 million people live in Cairo.
658,893 people live in Washington DC.
So it's false.
a. Given that y = f(x) and f(0) = -2, by the fundamental theorem of calculus we have
![\displaystyle \frac{dy}{dx} = 3x^2 + 4x + k \implies y = f(0) + \int_0^x (3t^2+4t+k) \, dt](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%203x%5E2%20%2B%204x%20%2B%20k%20%5Cimplies%20y%20%3D%20f%280%29%20%2B%20%5Cint_0%5Ex%20%283t%5E2%2B4t%2Bk%29%20%5C%2C%20dt)
Evaluate the integral to solve for y :
![\displaystyle y = -2 + \int_0^x (3t^2+4t+k) \, dt](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%20%3D%20-2%20%2B%20%5Cint_0%5Ex%20%283t%5E2%2B4t%2Bk%29%20%5C%2C%20dt)
![\displaystyle y = -2 + (t^3+2t^2+kt)\bigg|_0^x](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%20%3D%20-2%20%2B%20%28t%5E3%2B2t%5E2%2Bkt%29%5Cbigg%7C_0%5Ex)
![\displaystyle y = x^3+2x^2+kx - 2](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%20%3D%20x%5E3%2B2x%5E2%2Bkx%20-%202)
Use the other known value, f(2) = 18, to solve for k :
![18 = 2^3 + 2\times2^2+2k - 2 \implies \boxed{k = 2}](https://tex.z-dn.net/?f=18%20%3D%202%5E3%20%2B%202%5Ctimes2%5E2%2B2k%20-%202%20%5Cimplies%20%5Cboxed%7Bk%20%3D%202%7D)
Then the curve C has equation
![\boxed{y = x^3 + 2x^2 + 2x - 2}](https://tex.z-dn.net/?f=%5Cboxed%7By%20%3D%20x%5E3%20%2B%202x%5E2%20%2B%202x%20-%202%7D)
b. Any tangent to the curve C at a point (a, f(a)) has slope equal to the derivative of y at that point:
![\dfrac{dy}{dx}\bigg|_{x=a} = 3a^2 + 4a + 2](https://tex.z-dn.net/?f=%5Cdfrac%7Bdy%7D%7Bdx%7D%5Cbigg%7C_%7Bx%3Da%7D%20%3D%203a%5E2%20%2B%204a%20%2B%202)
The slope of the given tangent line
is 1. Solve for a :
![3a^2 + 4a + 2 = 1 \implies 3a^2 + 4a + 1 = (3a+1)(a+1)=0 \implies a = -\dfrac13 \text{ or }a = -1](https://tex.z-dn.net/?f=3a%5E2%20%2B%204a%20%2B%202%20%3D%201%20%5Cimplies%203a%5E2%20%2B%204a%20%2B%201%20%3D%20%283a%2B1%29%28a%2B1%29%3D0%20%5Cimplies%20a%20%3D%20-%5Cdfrac13%20%5Ctext%7B%20or%20%7Da%20%3D%20-1)
so we know there exists a tangent to C with slope 1. When x = -1/3, we have y = f(-1/3) = -67/27; when x = -1, we have y = f(-1) = -3. This means the tangent line must meet C at either (-1/3, -67/27) or (-1, -3).
Decide which of these points is correct:
![x - 2 = x^3 + 2x^2 + 2x - 2 \implies x^3 + 2x^2 + x = x(x+1)^2=0 \implies x=0 \text{ or } x = -1](https://tex.z-dn.net/?f=x%20-%202%20%3D%20x%5E3%20%2B%202x%5E2%20%2B%202x%20-%202%20%5Cimplies%20x%5E3%20%2B%202x%5E2%20%2B%20x%20%3D%20x%28x%2B1%29%5E2%3D0%20%5Cimplies%20x%3D0%20%5Ctext%7B%20or%20%7D%20x%20%3D%20-1)
So, the point of contact between the tangent line and C is (-1, -3).
You have to multiply 36 times 4 =144 . So you do this like this (30 times 4) +(4 times 6)= so (120)+(24)= 144. Answer is 144